2015
DOI: 10.1002/lary.25484
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different bronchoalveolar lavage methods on tracheobronchial foreign body patients

Abstract: 1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Out of the 14,471 cases in this review article, only 2551 reported a positive history of FBA and its associated complications. The rate of this event was 100% in Denmark 46 and Italy, 47 whereas India 17,18 (57.9%) and China 6,7,20–26,34,36,37 (52.8%) had the lowest witness rates. As presented in Table 4, Asian patients reported a higher number of choking history, while Europeans had fewer witnesses of FBA.…”
Section: Results and Descriptions Of The Included Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…Out of the 14,471 cases in this review article, only 2551 reported a positive history of FBA and its associated complications. The rate of this event was 100% in Denmark 46 and Italy, 47 whereas India 17,18 (57.9%) and China 6,7,20–26,34,36,37 (52.8%) had the lowest witness rates. As presented in Table 4, Asian patients reported a higher number of choking history, while Europeans had fewer witnesses of FBA.…”
Section: Results and Descriptions Of The Included Studiesmentioning
confidence: 93%
“…After screening and reviewing the articles, 14,471 cases were evaluated with 2852 females (40%) and 4290 males (60%) being the majority. India, 17,18 Pakistan, 19 and China 7,20–26 had the highest male‐to‐female ratios, while Sweden 14 and Iran 8 had ratios closer to 1. We were unable to determine the precise number of pediatric males and females from 12 articles 6,27–37 .…”
Section: Results and Descriptions Of The Included Studiesmentioning
confidence: 98%
“…Clinicians can use this reaction to decrease mucosal bleeding during surgery and procedures (Kuan et al, ; Valdes, Al Badaai, Bogado, & Samaha, ; Zhu & Meng, ). The benefit of airway administration of epinephrine to stop bleeding has been recognized, and topical application of local anesthetics with epinephrine is used to promote recovery in tracheobronchial foreign body (TFB) patients and reduce the incidence of complications in BAL with bronchoscopy (Luo, Ma, Guo, Wang, & Ren, ). Lange et al () found that nebulization of 1:1,000 epinephrine reduced airway blood flow and attenuated pulmonary dysfunction in sheep subjected to severe smoke inhalation injury.…”
Section: Disscusionmentioning
confidence: 99%